Total/Legs Dual-Energy X-Ray Absorptiometric Index In Differentiation Of Normal Body Fat Distribution In Healthy Women From Cushing’s And Non Cushing Obese - Slavica Shubeska Stratrova; Dejan Spasovski; Slagjana Maksimoska; Kocevska, Ana (My University, 2020)
Objectives: Cushing’s syndrome (CS) is associated with weight gain and extreme central, visceral, abdominal obesity. Obese individuals differ not only according to the degree of excess fat which they store, but also in the regional distribution of the fat within the body. It was discovered by dual-energy x-ray absosrptiometry (DXA) that BMI increase in healthy women was associated with a more pronounced abdominal body fat distribution, indicating substantially higher risk for development of metabolic and cardiovascular complications. Because of that, the primary purpose of this study was to develop a set of DXA normative standards of normal body fat distribution and to determine their normal cut-off point values that best differentiate healthy women with normal BMI and body composition from CS and non CS obese women and exclude abdominal obesity in women with no increased health risks. Material and Methods: DXA assessment of body composition and body fat distribution was performed in three groups of women, each consisting of 21 subjects: 1st group of Cushing’s syndrome with clinically confirmed CS with Body Mass Index (BMI) (30.03±6.49 kg/m2 ) and age of 42.98±13.27 years, 2nd group of obese women (O) with BMI 35±2 kg/m2 and age of 43±10yr and 3rd group of healthy women with normal BMI values 22±1.4 kg/m2 and age 41±12 yr. Total (To) and legs (L) tissue mass were determined (To-T, L-T) and To and L fat mass (To-F, L-F), as well as their ratios To/L-T and To/L-F. To/L-T%f and To/L-F% were also determined. Their cut-off point values of normal body fat distribution were determined that best differentiated group C from CS and O. Sensitivity (S), specificity (Sp), positive predictive value (PPV), negative predictive value (NPV) and DG (diagnostic accuracy) of these idexes were determined. Results: To/L-T values in CS were 3.55±0.33 and 3.2±0.19 in O, significantly higher compared to 2.7±0.16 in C (p<0.0001). To/L-T cut-off point value of 2.95 and To/L-F of 2.7 best differentiated CS from C for DG of 97.22%, S and NPV value of 100%, Sp and PPV value of 94.44%. To/L-T cut-off point value of 2.95 differentiated O from C for S of 100%, Sp of 88.89%, PPV of 90% and NPV of 88.9% and DG of 94.44%. To/L-F cut-off point value of 2.7 differentiated O from C for S of 100%, Sp of 94.44%, PPV of 94.74%, NPV of 100% and DG of 97.22%. To/L-T%f and To/L-F% indexes differentiated the examined groups with lower diagnostic accuracy. Conclusion: To/L-T and To/L-F DXA indexes differentiated CS and O from healthy women with normal BMI with high diagnostic accuracy and confirmed abdominal, visceral obesity in CS. Also, lower values than determined cut-off point values of these indexes confirmed normal body fat distribution in control healthy women with normal BMI. They could be used as DXA diagnostic indexes of normal body fat distribution. To/L-T%f and To/L-F% indexes differentiated the examined groups with lower diagnostic accuracy and have no diagnostic importance in evaluation of the body fat distribution.
Keywords: Cushing’s Syndrome; abdominal obesity; dual-energy x-ray absorptiometry